Praca i prawne podstawy jej wykonywania - Wiśniewski, Janusz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2013)
The author makes an attempt to analyze the essence of work in the context of the growing demand on innovativeness and “practical approach”, in which corporate stakeholders try to utilize all opportunities and resources within changes outlined by an increasingly globalized world. The world is based on network structures, knowledge, and the free exchange of information, people and capital. At the same time, an attempt is made to indicate that the work itself does not constitute a criterion which decides which legal form should be applied to it. It is confirmed that in the post-capitalist economy work has returned to its roots. New, flexible forms of work, such as telework, temporary work and self-employment change many properties of employment typical of a modern society to have lived in the past 100 years. Work can also be performed based on civil-law contracts (work under a non-employment contract). This issue has led to ongoing discussions regarding the need of the equal rights for those employed within civil-law contracts and people working based on employment contracts. However, the subject of this equality and awarded protection poses a dilemma.
WORK AND LEGAL FORMS OF ITS EXECUTION
Keywords: essence of work; creative of work; freedom of work principle; work protection; various employment contracts; civil-law agreements